2018
DOI: 10.1016/j.neuroimage.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Robust is not necessarily reliable: From within-subjects fMRI contrasts to between-subjects comparisons

Abstract: Advances in cognitive and affective neuroscience come largely from within-subjects comparisons, in which the functional significance of neural activity is determined by contrasting two or more experimental conditions. Clinical and social neuroscience studies have attempted to leverage between-subject variability in such condition differences to better understand psychopathology and other individual differences. Shifting from within-to between-subjects comparisons requires that measures have adequate internal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 28 publications
15
86
0
Order By: Relevance
“…This is comparable to the ICCs of the behavioral data for the overall conditions. However, for reaction time, ICC for the incongruent versus congruent contrast was reduced relative to the overall conditions, further supporting findings of Infantolino et al () and Hedge et al (2018), that in addition to examining the reliability of neural measures, the behavioral measures should be assessed as well. Additionally, the fact that some conditions (e.g., all faces, congruent or incongruent) had a larger number of trials than other contrasts, such as conflict monitoring, needs to be considered; poor reliability in those trials may, at least in part, relate to low statistical power (Brown et al, ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is comparable to the ICCs of the behavioral data for the overall conditions. However, for reaction time, ICC for the incongruent versus congruent contrast was reduced relative to the overall conditions, further supporting findings of Infantolino et al () and Hedge et al (2018), that in addition to examining the reliability of neural measures, the behavioral measures should be assessed as well. Additionally, the fact that some conditions (e.g., all faces, congruent or incongruent) had a larger number of trials than other contrasts, such as conflict monitoring, needs to be considered; poor reliability in those trials may, at least in part, relate to low statistical power (Brown et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…Thus, considering a trade-off between the complexity of the model, or contrast, and its interpretability is important when assessing test-retest reliability, especially when an intervention is introduced between scans. Direct comparison of active contrasts (e.g., incongruent minus congruent) showed poor reliability also in other neuroimaging studies (e.g., [Infantolino, Luking, Sauder, Curtin, & Hajcak, 2018]); however, main effects, or conditions, such as congruent or incongruent showed comparatively better reliability. Furthermore, observed differences in reliability may also be related to the nature of the task and more so to the similarity of its trials.…”
Section: Discussionmentioning
confidence: 61%
“…(see supporting information), in line with recent work has suggested that researchers report the reliability of both types of measures (Infantolino, Luking, Sauder, Curtin, & Hajcak, 2018). When selecting measurement indices of unpredictable threat processing, researchers may wish to take into account their reported reliabilities.…”
supporting
confidence: 71%
“…Change scores, which are produced by subtracting two measures, will always have lower reliability than their constituent measures (29) . Currently, the majority of task-fMRI measures are based on contrasts between conditions (i.e., change scores), undermining their reliability (45) . However, the widespread use of contrasts in task-fMRI is largely a vestige of experimental cognitive neuroscience.…”
Section: ) Be Wary Of Difference Scores (Ie Contrasts)mentioning
confidence: 99%